Evidence for a role of oestrogen receptor‐related receptor in the regulation of male sexual behaviour in the moth Agrotis ipsilon. Issue 4 (29th March 2017) - Bozzolan, F.; Durand, N.; Demondion, E.; Bourgeois, T.; Gassias, E.; Debernard, S.
Abstract: The oestrogen receptor‐related receptors (ERRs) are orphan nuclear receptors that were originally identified on the basis of their close homology to the oestrogen receptors. The three mammalian ERR genes participate in the regulation of vital physiological processes including reproduction, development and metabolic homeostasis. Although unique ERRs have been found in insects, data on the function and regulation of these receptors remain sparse. In the present study, a 2095‐bp full‐length cDNA encoding an ERR, termed AiERR, was isolated from males of the moth Agrotis ipsilon and deposited in the GenBank database under the accession number KT944662. The predicted AiERR protein shared an overall identity of 47–82% with other known insect and mammalian ERR homologues. AiERR exhibited a broad tissue expression pattern with the detection of one transcript of approximately 2 kb in the primary olfactory centres, the antennal lobes (AL). In adult males, the amount of AiERR mRNA in the AL increased concomitantly with age and responses to the female‐emitted sex pheromone. Moreover, AiERR knockdown induced an inhibition in the sex pheromone‐orientated flight of male. Using A. ipsilon as a model, our study demonstrates that the insect ERR is critical for the performance of male sexual behaviour, probably by acting on central pheromone processing.